Treatment of female stress urinary incontinence with Erbium-YAG laser in non-ablative mode. (September 2016) - Pardo, Jack I.; Solà, Vicente R.; Morales, Andrea A.
Abstract: Objective: To evaluate the efficacy of laser photothermal therapy in a group of Chilean women with SUI. Material and methods: Longitudinal prospective study based on 42 women with mild-to-severe SUI, intervened with non ablative Er:YAG laser, between July 2014 and October 2015, in Santiago, Chile. The therapy efficacy was evaluated through the difference between every patient's scores obtained, before and after treatment, with the International Consultation on Incontinence Questionnaire – Urinary Incontinence Short Form (ICIQ-SF), at a confidence level of 95%. Also, the patient satisfaction with treatment was reported through an ordinal scale. Results: ICIQ-SF median score was 11 before treatment and 3 after 6 months, with a significant difference per patient ( p < 0.001). 78.6% ( n = 33) reported improvement and 38.1% ( n = 16), a complete healing of SUI at follow up. 66.7% ( n = 28) reported high satisfaction and 81.8% ( n = 27) of sexually active women, also reported improvement of sexual gratification. Only mild pain during the procedure was reported as adverse effect. Conclusions: Based on this short-term pilot study, non-ablative Er:YAG laser procedure seems to be a safe and efficacious alternative for patients with SUI. Further controlled studies will help to validate the use of non-ablative Er:YAG for treatment of SUI.